GAMBARAN PENGETAHUAN IBU HAMIL TENTANG PENCEGAHAN ANEMIA PADA IBU HAMIL - Ermi Lilianda Alang; Ninick Corea Fernandez (STKIP Subang, 2026)
Anaemia during pregnancy remains a major challenge in efforts to improve maternal and infant health. In pregnant women, anemia is defined as a condition where hemoglobin levels are below 11 g/dL. The impact of anemia extends beyond the mother; it also increases the risk of preterm birth, low birth weight, and impaired fetal growth, as well as raising morbidity and mortality rates for both mothers and infants.The aim of this study is to determine the knowledge of pregnant women regarding anaemia during pregnancy.This study employs a descriptive research design. The sample consists of 68 pregnant women within the working area of ​​the Naibonat Community Health Center Proportional random sampling was used as the sampling technique, and data analysis was conducted using frequency distribution.The result interpreted based on the variables studied, using criteria of good, sufficient, and lacking The results indicate that, among pregnant women in the Naibonat Community Health Center service area, 27 (39.7%) had lacking knowledge regarding anaemia during pregnancy, 25 (36.8%) had sufficient knowledge, and 16 (23.5%) had good knowledge.The majority of pregnant women fall into the